Pengaruh Advertising Attractiveness, Influencer Marketing, Online Customer Reviews terhadap Purchase Decision pada brand No Void Minds di TikTokShop. - Fathurrahman; Farid; Rizki Amalia (Yayasan Sagita Akademia Maju, 2026)
The development of digital technology has changed consumer behavior, particularly in purchasing activities through social commerce platforms such as TikTok Shop. This study aims to analyze the influence of advertising attractiveness, influencer marketing, and online customer reviews on purchase decisions for the No Void Minds brand. The study used a quantitative approach with an explanatory research design, involving 152 respondents selected through a purposive sampling technique in Banda Aceh City. Data were collected from respondents through an online questionnaire. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that all independent variables had a positive and significant effect on purchase decisions. Advertising attractiveness was the most dominant factor, followed by influencer marketing and online customer reviews. The R-square value of 0.601 indicates that 60.1% of the variation in purchase decisions can be explained by these three variables. These results emphasize the importance of creative and visual advertising appeal in driving purchase decisions, which is strengthened by the credibility of influencers and customer reviews on digital platforms.